Risk and Protective Factors for Gun Violence in Male Juvenile Offenders. Issue 3 (4th May 2021) - Pardini, Dustin; Beardslee, Jordan; Docherty, Meagan; Schubert, Carol; Mulvey, Edward
ABSTRACT: Objective: To examine several risk and protective factors as predictors of future gun violence among male juvenile offenders. Method: Data came from a longitudinal cohort of 1, 170 male juvenile offenders (42.1% Black; 34.0% Latino; 19.2% White) ages 14–19 who were adjudicated for a serious offense. Interviews were conducted with participants every 6 months for 3 years and then annually for 4 years. The outcome was self-reported gun violence assessed at each follow-up. The time-lagged predictors included several self-reported risk factors (i.e., gun carrying, non-gun violence, drug dealing, heavy drinking, poor impulse control, rewards for crime, peer gun carrying, peer non-gun delinquency, gang membership) and protective factors (i.e., concern for others, expectations, and aspirations for work/family, religious beliefs, adult social supports). The data were analyzed using generalized estimating equation models. Results: There were 266 participants who reported engaging in gun violence at one or more assessments. Gun carrying was a significant predictor of future gun violence; however, nearly half (49%) of the juveniles who reported gun carrying across the repeated assessments did not report engaging in gun violence. Besides gun carrying, several risk (i.e., drug dealing, heavy drinking, rewards for crime, gang membership, peer gun carrying) and protective (i.e., concern for others, aspirations for work/family, religious beliefs, adult social supports) factors significantly predicted gun violence, after controlling for their co-occurrence (Risk factor odds ratios = 1.18–1.50; Protective factor odds ratios =.44-.87; p s<.05). Conclusions: Interventions designed to prevent gun violence among juvenile offenders should reduce targeted risk factors, while strengthening protective factors that may offset these risks.